Pests and diseases on Falcataria moluccana trees in agroforestry systems with pineapple in East Java, Indonesia - SRI RAHAYU; ANANTO TRIYOGO; SITI M. WIDYASTUTI; MUSYAFA’ MUSYAFA’; FIQRY ARDIANYAH (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rahayu S, Triyogo A, Widyastuti SM, Musyafa’, Ardianyah F. 2021. Pests and diseases on Falcataria moluccana trees in agroforestry systems with pineapple in East Java, Indonesia. Biodiversitas 22: 2779-2788. The agroforestry system using Falcataria moluccana (Sengon) and Ananas comosus (pineapple) is considered as a profitable intercropping system in Indonesia. To make it viable, it is necessary to evaluate the effect of mixed cropping on the incidence and severity of diseases and pests on Sengon trees and apply management measures. The present study was conducted (i) to assess the pest and disease problems on Sengon trees in the agroforestry system and (ii) to identify the most harmful pathogen/pest which affects the growth and causes mortality of Sengon trees at the beginning of intercropping and after the removal of pineapple from the system.  Incidence of pests and diseases were assessed in 3 replicate blocks with one-year-old Sengon trees mixed with pineapple, and in another 3 plots with four-year-old Sengon trees from where pineapple was removed after harvesting. Sengon and pineapple were planted in the plots using alley cropping method with 3 x 4 m2 spacing. The results showed that there were no significant pest and disease problems on pineapple. However, Sengon was infested by the white grub Lepidiota stigma, gall rust caused by the fungus Uromycladium falcatarium, the stem borer Xystrocera festiva, and mistletoe Scurrula sp. However, stem borer and gall rust were the only pest and disease issues recorded in the monocultures of Sengon in Indonesia. The occurrence of stem borer and gall rust disease had a significant effect on the diameter growth of trees and in some instances, these caused mortality of one-year-old trees. Significant mortality of four-year-old trees was caused by mistletoe infestation only. Although the incidence of gall rust and stem borer in the agroforestry system was not significantly low compared to the monoculture, the former had wider spacing between trees, more open canopy and resultant low humidity and faster wind speed reduced the severity of the gall rust disease and stem borer attack. However, the intercropping resulted in the white grub attack on young Sengon trees which calls for application of contaminant-free fertilizers in pineapple plantings.